Horizontaltragfähigkeit von Wänden aus Leichtbeton-Schalungssteinen - Experimente und numerische Modellierung - Bacht, Tobias (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2015)
This work deals with the experimental , static - cyclic testing of large-scale tests on walls made from hollow blocks. Based on this non-linear finite element models are developed and verified using the extensive experimental data ,whereby a semi - empirical design concept could finally be derived for hollow concrete masonry walls by a parametric study .